β-TCP from 3D-printed composite scaffolds acts as an effective phosphate source during osteogenic differentiation of human mesenchymal stromal cells - Hatt, Luan P.; van der Heide, Daphne; Armiento, Angela R.; Stoddart, Martin J. (Frontiers in Cell and Developmental Biology, 2023)
Human bone marrow-derived mesenchymal stromal cells (hBM-MSCs) are often combined with calcium phosphate (CaP) -based 3D-printed scaffolds with the goal of creating a bone substitute that can repair segmental bone defects. In vitro, the induction of osteogenic differentiation traditionally requires, among other supplements, the addition of β-glycerophosphate (BGP), which acts as a phosphate source. The aim of this study is to investigate whether phosphate contained within the 3Dprinted scaffolds can effectively be used as a phosphate source during hBM-MSC in vitro osteogenesis. hBM-MSCs are cultured on 3D-printed discs composed of poly(lactic-co-glycolic acid) (PLGA) and β-tricalcium phosphate (β-TCP) for 28 days under osteogenic conditions, with and without the supplementation of BGP. The effects of BGP removal on various cellular parameters, including cell metabolic activity, alkaline phosphatase (ALP) presence and activity, proliferation, osteogenic gene expression, levels of free phosphate in the media and mineralisation, are assessed. The removal of exogenous BGP increases cell metabolic activity, ALP activity, proliferation, and gene expression of matrix-related (COL1A1, IBSP, SPP1), transcriptional (SP7, RUNX2/SOX9, PPARγ) and phosphate-related (ALPL, ENPP1, ANKH, PHOSPHO1) markers in a donor dependent manner. BGP removal leads to decreased free phosphate concentration in the media and maintained of mineral deposition staining. Our findings demonstrate the detrimental impact of exogenous BGP on hBM-MSCs cultured on a phosphate-based material and propose β-TCP embedded within 3Dprinted scaffold as a sufficient phosphate source for hBM-MSCs during osteogenesis. The presented study provides novel insights into the interaction of hBM-MSCs with 3D-printed CaP based materials, an essential aspect for the advancement of bone tissue engineering strategies aimed at repairing segmental defects.